2020
DOI: 10.3389/fbioe.2020.00256
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Novel Long Non-coding RNA Biomarkers for Early Diagnosis of Oral Squamous Cell Carcinoma

Abstract: Long non-coding RNAs (lncRNAs) are recently emerging as a novel promising biomarker for cancer diagnosis and prognosis. Despite these previous investigations, the expression pattern and diagnostic role of lncRNAs in oral squamous cell carcinoma (OSCC) remain unclear. In this study, we identified six novel lncRNA biomarkers (LINC01697, LINC02487, LOC105376575, AC005083.1, SLC8A1-AS1, and U62317.1) from a list of 29 differentially expressed lncRNAs using the least absolute shrinkage and selection operator (LASSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…The lncRNA FGF10‐AS1 may play a role in the development of many cancers. In addition, the lncRNA LINC01697 also showed good predictive performance in the diagnosis and prognosis of lung squamous cell carcinoma or oral squamous cell carcinoma [ 25 , 26 ]. The other lncRNAs in this model have not been reported in cancer and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA FGF10‐AS1 may play a role in the development of many cancers. In addition, the lncRNA LINC01697 also showed good predictive performance in the diagnosis and prognosis of lung squamous cell carcinoma or oral squamous cell carcinoma [ 25 , 26 ]. The other lncRNAs in this model have not been reported in cancer and require further research.…”
Section: Discussionmentioning
confidence: 99%
“…For the mechanism, they revealed that LINC02487 directly binds to USP17, a deubiquitinating enzyme, and regulates cell migration and invasion through the USP17-SNAI1 axis in a process that involves epithelial-mesenchymal transition (EMT) [ 28 ]. Li et al also introduced LINC02487as Biomarker for Early Diagnosis of Oral Squamous Cell Carcinoma [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless these treatment approaches are not effective in improving the clinical outcome of OSCC patients ( Zanoni et al, 2019 ). Because traditional surgical treatment cannot effectively improve the prognosis of OSCC patients, searching for reliable biomarkers is essential to improve the diagnosis and treatment of OSCC in the early stages of the disease ( Li et al, 2020 ; Jia et al, 2021 ). Based on previous studies, abnormally expressed lncRNAs have been recognized as moderators of tumor evolution in different cancers, exerting procarcinogenic function or anticancer function by regulating the malignant biological behaviors of tumors directly or indirectly, including processes such as proliferation, migration, invasion, and glycolysis ( Schmitt and Chang 2016 ; Ahadi 2020 ; Song and Kim 2021 ).…”
Section: Discussionmentioning
confidence: 99%